Bunuel, Thanks for the correction

Answer = D

Numerator\(1 - x^{16}\)

\(= (1 + x^8) (1 - x^8)\)

\(= (1 + x^8) (1 + x^4) (1 - x^4)\)

\(= (1 + x^8) (1 + x^4) (1 + x^2) (1 - x^2)\)

\(= (1 + x^8) (1 + x^4) (1 + x^2) (1 + x) (1 - x)\)

Denominator\((1 + x^8) (1 + x^4) (1 + x^2) (1 + x)\)

Expanded / simplified equation would be

\(\frac{(1 + x^8) (1 + x^4) (1 + x^2) (1 + x) (1 - x)}{(1 + x^8) (1 + x^4) (1 + x^2) (1 + x)}\)

= 1 - x

Answer = D

_________________

Kindly press "+1 Kudos" to appreciate